Women Negotiating Feminism and Science Fiction Fandom The Case of the "Good" Fan - Yodovich, Neta. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book follows the ways in which women negotiate and navigate between their feminist identities and their belonging to science fiction fandoms that at times disregard or dismiss them. It explores frictions and discords, including those between feminist women fans and other members in their communities, and between the fan and the object of her fandom. This book examines the intersection of fandom and feminism through the lenses of gender, ethnicity and age, and provides an in-depth and intersectional perspective on fan communities and the layered discrimination and marginalization enfolded in them. Based on 40 in-depth interviews with women fans of Star Wars and Doctor Who, this book highlights the different aspects of a feminist woman fan's identity: becoming, being, belonging, representing, and reconciling. Each chapter in this book unravels the complexity, ambivalence, and contradictions between feminism and fandom, and reveals the tactics women develop to overcome and harmonize them. Neta Yodovich is a postdoctoral researcher who is currently studying cultural policy in a research project funded by the EU Horizon 2020 framework. She completed her PhD in Sociology at the University of Manchester. Her PhD research on feminist women fans serves as the basis for this book. She has previously published peer-reviewed journal articles about women fans, gamers, and representations of singlehood in popular culture in Sociology, Feminist Media Studies, Games and Culture, Women's Studies in Communication, and the European Journal of Women's Studies.
1. Introducing Feminism and Fandom -- 2. Becoming a Feminist Fan -- 3. Being a Feminist Fan -- 4. Belonging as a Feminist Fan -- 5. Representing Women and Feminism in Fandom -- 6. Reconciling Feminism and Fandom -- 7. Finding a Space(ship) of One's Own.
Keywords: Audiences; Popular Culture; Gender identity in mass media; Fan and Audience Studies; Popular Culture; Media and Gender